Plantar pressure profiles of athletes with and without ankle sprains while walking barefoot and in sport shoes. (2nd January 2016) - Milford, Jennifer; Sole, Christopher Charles; Sole, Gisela
Abstract : Plantar pressures have been investigated as contributors to the etiology of ankle sprains. Footwear has not been explored as a potential factor influencing plantar pressures in participants with previous ankle sprains. The aim of this study was to compare walking barefoot and shod plantar pressure distributions between participants with a recent ankle sprain and uninjured controls. Seventeen physically active individuals with a lateral ankle sprain sustained within the past two years, and 20 healthy controls walked at a self-selected speed across a RS-Footscan® pressure plate. Personal sports shoes were assessed for mediolateral asymmetry at the forefoot and heel. Seven walking trials were performed barefoot and shod. Mediolateral plantar pressure ratios for (1) the hindfoot and (2) the forefoot for the barefoot and the shoe conditions were processed. Two-way repeated measure ANOVAs (group × condition) were calculated for each of the two dependent variables and stance duration. Post-hoc testing with Bonferroni corrections was conducted when significant effects were found. Twelve (32%) of the thirty-seven shoes had neutral design and/or wear, twenty-four (65%) had lateral and one (3%) had medial asymmetry. There were no differences between the injured and control groups for forefoot and hindfoot plantar pressure ratios while walking barefoot or in shoes. However, wearing shoes increased medial forefoot pressure for the injured group and lateral hindfoot pressures in the controls compared to barefoot walking. Plantar pressure profiles were similar in participants with ankle sprains and controls walking barefoot. Walking in well-habituated footwear caused different adaptive strategies in the two groups. Footwear affects plantar pressures while walking, and the influence of mediolateral asymmetric footwear on lateral ankle sprains and recurrence needs further exploration.